The Influence of Management-Based Leadership on Improving to Human Resource Performance in Konawe District Health Center: Management-Based Leadership - Azlimin Azlimin; Adriatman Rasak; Apriyanto Aprianto (STIKes Mandala Waluya Kendari, 2023)
Background: Some health program in the Konawe District Health centres has not reached the national target including the percentage coverage of K4 maternal health (67.04%) compared to the target (90%), and exclusive breastfeeding for infants aged 0-6 months has reached 65.69% compared the target of 85%. The purpose of this study was to determine the influence of management-based leadership in the Konawe District Health Centere. Methods: The research method usedexploratory research that emphasizes aspects of influence between research variables with hypothetical tests and the description contains descriptions this focuses solely on the influence of variables. Results: This studyshow that Leadership has a positive and significant effect on the Management Function. The direction of influence of this relationship is positive which means that the better the leadership, the implementation of management functions will also be better,Leadership has a positive and significant effect on HR Performance. The direction of influence of this relationship is positive which means that the better the leadership, the better the HR performance produced and the Management Function has a positive and significant effect on HR Performance.The direction of influence of this relationship is positive which means that the better the management function, thebetter the HR performance produced will also be better. Conclusion: leadership has a positive and significant effect on the management function, leadership has a positive and significant effect on HR performance and Management function has a positive and significant effect on HR Performance.